(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2001)
The present work has an aim to quicken the adaptation process through the volitional optimization of reduction the minutary volume of breathing and the using exponent of oxygen raises. During the optimal volitional reduction of minutary volume breathing (OVR of MVB) prolonged the breathing phases to 3-5-7 seconds. The prolonged trainings of OVR of MVB brings to breathing frequency automation and respiration center works in a new rythm. As a result the frequency of breathing movement in a minute and free no volutional breathing to 15, 16 in a minute. During that reducted the minutary volume of breathing and corresponding the volume of dead space (which is not involved in exchange of gases) thanks to it the volume of air presented in exchange of gases visible increases. The one-month OVR of MVB trainings with mental and physical activity brings to physiological and biochemical changes in external and tissue breathing. That brings to increase of the oxygen using (which is involved in minutary volume of breathing) and the level of aerob breathing.